PENUH PANGGILANMENYELESAIKAN PERTANDINGAN SAMPAI AKHIR BERDASARKAN 2 TIM 4:1-8 - Indria Dwijayanti; Alfrini, Fitriani Belo, Roslina Arungbua' (Adisam Publisher, 2025)
Attitude in life is the foundation of the life of a servant of God. Was there at the time and earnest in his ministry. Where can we find a way to live in God’s love. Paul alluded to the teaching of God as a judge. In this awareness it should also be an inspiration that makes Timothy serve more seriously.